ANALISIS PENILAIAN KINERJA KEUANGAN MENGGUNAKAN PENERAPAN ECONOMIC VALUE ADDED. Studi Kasus: Pada PT. Binaartha Parama - Winarno, Slamet Heri (MONETER - JURNAL AKUNTANSI DAN KEUANGAN, 2014)
This Study aims to determine the company's financial performance is studied based on the analysis of Economic value added (EVA) for the year 2011 and 2012 on PT Binaartha Parama. The method used is descriptive analysis using time series data. The data used are the financial statements of the balance sheet and income statement for the period in 2011 and 2012. The results showed that the company's financial performance in 20011 and 2012 showed the unfavorable conditions in which the company is not able to create value-added enterprises, and therefore contributes to the formation of capital investment from investors. Keywords : EVA Method, Financial Performance